Paediatric hiv in south africa: an overview for physiotherapists - J. Potterton; H. van Aswegen (AOSIS, 2006)
Paediatric HIV is a major cause of morbidity and mortality in South African children. Physiotherapists working in the government sector are seeing large numbers of HIV infected children on a daily basis. This paper provides a general overview of paediatric HIV. Common conditions associated with HIV infection are highlighted and the possible role of physiotherapy is discussed. Suggestions for research on the role of physiotherapy in the management of children with HIV are made.